2002
DOI: 10.1074/jbc.m204645200
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a Short Highly Conserved Amino Acid Sequence as the Functional Region Required for Posttranscriptional Autoregulation of the Cystathionine γ-Synthase Gene in Arabidopsis

Abstract: Cystathionine ␥-synthase (CGS) catalyzes the first committed step of Met biosynthesis in plants. We have previously shown that expression of the gene for CGS is feedback-regulated at the level of mRNA stability, and that the amino acid sequence encoded by the first exon of the CGS gene itself is responsible for the regulation (Chiba, Y., Ishikawa, M., Kijima, F., Tyson, R. H., Kim, J., Yamamoto, A., Nambara, E., Leustek, T., Wallsgrove, R. M., and Naito, S. (1999) Science 286, 1371-1374). To identify the funct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
74
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 50 publications
(75 citation statements)
references
References 28 publications
1
74
0
Order By: Relevance
“…All subsequent mto1 alleles were also found to be located within this region. Alaninesubstitution experiments identified a short stretch of amino acid sequence, Arg-Arg-Asn-Cys-Ser-Asn-IleGly-Val-Ala-Gln, that covers the mto1 mutation sites that is important for the regulation, which is now referred to as the MTO1 region (Ominato et al 2002) (Figure 3). As a result of the mutation within the CGS exon 1 coding sequence, CGS mRNA levels were two-to four-fold higher in mto1 than in wild-type plants, which is reflected by elevated levels of CGS protein and enzyme activity (Chiba et al 1999;Ominato et al 2002).…”
Section: Cgs Enzyme Is Feedback Regulated At the Level Of Mrna Stabilmentioning
confidence: 99%
See 2 more Smart Citations
“…All subsequent mto1 alleles were also found to be located within this region. Alaninesubstitution experiments identified a short stretch of amino acid sequence, Arg-Arg-Asn-Cys-Ser-Asn-IleGly-Val-Ala-Gln, that covers the mto1 mutation sites that is important for the regulation, which is now referred to as the MTO1 region (Ominato et al 2002) (Figure 3). As a result of the mutation within the CGS exon 1 coding sequence, CGS mRNA levels were two-to four-fold higher in mto1 than in wild-type plants, which is reflected by elevated levels of CGS protein and enzyme activity (Chiba et al 1999;Ominato et al 2002).…”
Section: Cgs Enzyme Is Feedback Regulated At the Level Of Mrna Stabilmentioning
confidence: 99%
“…Alaninesubstitution experiments identified a short stretch of amino acid sequence, Arg-Arg-Asn-Cys-Ser-Asn-IleGly-Val-Ala-Gln, that covers the mto1 mutation sites that is important for the regulation, which is now referred to as the MTO1 region (Ominato et al 2002) (Figure 3). As a result of the mutation within the CGS exon 1 coding sequence, CGS mRNA levels were two-to four-fold higher in mto1 than in wild-type plants, which is reflected by elevated levels of CGS protein and enzyme activity (Chiba et al 1999;Ominato et al 2002). Analysis of the regulation defect in mto1 revealed that wild-type CGS is negatively regulated in response to exogenous application of methionine, and that posttranscriptional regulation at the level of mRNA stability plays a major role (Chiba et al 1999).…”
Section: Cgs Enzyme Is Feedback Regulated At the Level Of Mrna Stabilmentioning
confidence: 99%
See 1 more Smart Citation
“…A. thaliana mto1 mutants that bear single amino acid sequence alterations within the MTO1 region abolish this feedback regulation, resulting in an over-accumulation of soluble Met (Ominato et al, 2002; for review, see Goto et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…A short amino acid sequence, termed the MTO1 region, 77-RRNCSNIGVAQ-87, encoded in the N-terminal region of CGS1, acts as the cis-element for this regulation (Ominato et al, 2002;Chiba et al, 2003). A. thaliana mto1 mutants that bear single amino acid sequence alterations within the MTO1 region abolish this feedback regulation, resulting in an over-accumulation of soluble Met (Ominato et al, 2002; for review, see Goto et al, 2005).…”
Section: Introductionmentioning
confidence: 99%